The implementation of Hudud Law in Malaysia: (with reference to theft and robbery) / Ainaa Bazilah Bakhori … [et al.] - Bakhori, Ainaa Bazilah; Mohd Johar, Ateera Hamidah; Mohd Abu Bakar, Azreen Fasya; Muhd Noor, Najhan Farhana (2012)
This research is carried out in order to propose the implementation of Hudud law for the offences of theft and robbery in Malaysia. In doing so, it will proof that there are loopholes on the current punishments for theft and robbery in the Penal Code (ACT 574). Thereby to fix the loopholes, it is imperative to incorporate Hudud punishments in the Penal Code (ACT 574). The method used in this research is the qualitative methodology. References are done to books, journals and reliable internet materials. Interviews were also conducted with academicians to get their views in the implementation of Hudud law in Malaysia from the social and legal perspectives. The academicians were Professor Madya Dr. Mohamed Azam Mohamed Adil and Emeritus Professor Datuk Dr. Hj. Shad Saleem Faruqi. A detailed review on statistics of crime rates for every state in Malaysia were also conducted in order to proof that theft and robbery offences are the main contributors for the high statistics crime rates in Malaysia. The goal for this research is to show the effectiveness of Hudud law in deterring society from committing the offences of theft and robbery. The effectiveness will be proven by comparing the statistics of theft and robbery between Malaysia and Pakistan. This research will also study the procedures that can be followed in order to make the incorporation of Hudud law a reality in Malaysia. Education to the public on the purpose of Hudud law is also important to avoid further misunderstanding.